Financing Constraints and the Cost of Capital: Evidence from the Funding of Corporate Pension Plans - Campbell, John L.; Dhaliwal, Dan S.; Schwartz, William C. (Review of Financial Studies, 2012)
We investigate the relation between firms' weighted average cost of capital and internal financial resources, using mandatory pension contributions as a proxy for internal financial resources. Rauh (2006) documents a negative association between mandatory pension contributions and capital expenditures. We find that an increase in mandatory pension contributions increases the cost of capital, but only for firms facing greater external financing constraints. Our results suggest that firms' cost of capital is an intervening variable that can explain Rauh's finding that mandatory pension contributions (i.e., internal financing constraints) result in foregone investment. Overall, we provide evidence consistent with recent studies (Rauh 2006; Almeida and Campello 2007) that conclude that financial market frictions affect real economic activity and, in particular, corporate investment. The Author 2011. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oup.com., Oxford University Press.